THE IMPLEMENTATION OF SAK EMKM AND ITS EFFECT ON MSME LOAN ACCEPTANCE - Siti Mubiroh; Zulfatun Ruscitasari (Universitas Airlangga, 2019)
MSMEs are the heart of the economy in a country. The existence of MSMEs can save the country from the economic crisis, as can be seen from the crises that occurred in 1998 and 2008. The number of unemployed can be overcome because the absorption of MSME workers reaches 96% of the total workforce in Indonesia. However, the sustainability of MSME operations is often constrained by access to funding. These constraints are caused by the lack of quality of MSME financial reports. Therefore banks or other financial institutions are more careful in providing loans to MSMEs. This study aims to determine the implementation of SAK EMKM by using variables of company size, educational background of the owner, and providing information and socialization of SAK EMKM. In addition, the purpose of this study is to examine the effect of SAK EMKM on the quality of MSME financial reports, and the effect of the quality of financial reports on MSME credit receipts. This study uses a quantitative approach with a survey method, namely distributing questionnaires to MSME actors in the Special Region of Yogyakarta. The sampling technique used was random sampling. The data was processed using SPSS with multiple regression analysis tools. The results of this study indicate that the variables of company size and educational background of MSME owners have no significant effect on the implementation of SAK EMKM. While the variable of providing socialization and information has a significant effect on the implementation of SAK EMKM. Then, the SAK EMKM implementation variable has a significant effect on the quality of financial statements, and the variable quality of financial reports has no significant effect on MSME credit receipts.